(untitled) (Biological Sciences - PJSIR, 2001)
The present communication deals with the electron impact studies on ethyl 2,3-dioxobutyrate-2-phenylhydrazones and related substituted phenylhydrazones containing electron releasing as well as electron withdrawing substituents on the phenyl nucleus. The formation of base peaks were greatly influenced by the nature of substituent in the phenyl nucleus. Neutral and radical loss from the aromatic subtituents were also found to depend upon the nature of groups. These hydra zones undergo thermal isomerisation to azo form which fragments subsequently to daughter ions in accordance with the azo structure having very low relative intensity and L